An exploration of the influences of supervisors of midwives in the context of the lifelong learning (continuing professional development) of practising midwives - Drury, Colleen A. (2012)
This study aimed to explore the influences of Supervisors of Midwives in the context of Lifelong Learning (continuing professional development) (CPO) of practising midwives.